PENGARUH PARIWISATA, MONEY SUPPLY, DAN PENDAPATAN PER KAPITA TERHADAP PERTUMBUHAN EKONOMI PADA LIMA NEGARA ASEAN PERIODE 2005 - 2015 - Lya Arizka Shabrina; Ahmad Zafrullah TN.; Firman Rosjadi Djoemadi (CALYPTRA, 2018)
The economic growth of the five ASEAN countries is influenced by various factors. The main purpose of this study is to analyze the influence of Tourism, Money Supply, and Per Capita Income on the Economic Growth of the five ASEAN countries in 2005-2015 period. To find out the research hypothesis used econometric model with the method of OLS (Ordinary Least Square), which is estimated using Eviews 6. From the analysis results can be concluded that the variable of Tourism, Money Supply, and Per Capita Incom based on test results together, all variables together -the same significant effect on the Economic Growth of the five ASEAN countries at a significance level of 5% with a probability of 9.731762. While individually, variable Income Per Capita have positive and insignificant effect to Economic Growth with coefficient 0.395975. Tourism variable has positive and insignificant effect to Economic Growth with coefficient of 0.029077. Money Supply variable has positive and significant effect to Economic Growth with coefficient of 0.03303.